Calculation Methods for Inter-Story Drifts of Building Structures. Issue 5 (May 2014) - Cai, Jian; Bu, Guobin; Yang, Chun; Chen, Qingjun; Zuo, Zhiliang
The current methods for calculating the inter-story harmful drift are evaluated, and new concepts of the inter-story average shear drift and the inter-story average rotation are proposed in this paper. The definitions and contents of the inter-story harmful and harmless drift are introduced. Four existing methods for calculating the harmful and harmless drift, including the secant method, tangent method, fixing floor method, and generalized shear deformation of region method are revisited, and the advantages as well as shortcomings of these methods are compared. Meanwhile, the misunderstanding in calculating the floor rotation is clarified. The inter-story average shear drift and the inter-story average rotation are proposed. In addition, the relationships among these proposed drifts and the harmful drift are derived, and are examined by the static and dynamic analysis of a simplified structural model. It demonstrates that the proposed drifts are effective in both static as well as dynamic analysis, and can be used for providing more specific information in the structural deformation analysis.